1993
DOI: 10.1901/jeab.1993.60-219
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Establishing Schedules With Wheel Running as Reinforcement in Rats

Abstract: In three experiments, access to wheel running was contingent on lever pressing. In each experiment, the duration of access to running was reduced gradually to 4, 5, or 6 s, and the schedule parameters were expanded gradually. The sessions lasted 2 hr. In Experiment 1, a fixed-ratio 20 schedule controlled a typical break-and-run pattern of lever pressing that was maintained throughout the session for 3 rats. In Experiment 2, a fixed-interval schedule of 6 min maintained lever pressing throughout the session for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 12 publications
2
122
1
1
Order By: Relevance
“…However, 30 minutes of running was found to have no effect on their brain dopamine activity [39]. Wheel running by rats and other small animal models occurs spontaneously and is a reinforcing behavior in that they will perform lever presses to engage in wheel running [40][41][42][43]. Moreover, wheel running produces a reinforcing aftereffect as measured by conditioned place preference after the exercise has stopped [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, 30 minutes of running was found to have no effect on their brain dopamine activity [39]. Wheel running by rats and other small animal models occurs spontaneously and is a reinforcing behavior in that they will perform lever presses to engage in wheel running [40][41][42][43]. Moreover, wheel running produces a reinforcing aftereffect as measured by conditioned place preference after the exercise has stopped [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, running almost exclusively occurs at night as many other appetitive behaviors (Eikelboom and Mills, 1988). It is generally agreed that wheel running is naturally rewarding and strongly depends on animal motivation to perform this behavior (Belke, 1997;Iversen, 1993;Yu et al, 2005). It has been demonstrated that the pattern of operant responding to gain access to a wheel was similar to those observed for conventionally accepted consummatory reinforces such as food and water (Belke, 1997).…”
Section: Voluntary Running As An Indicator Of Manganese-induced Toxicitymentioning
confidence: 98%
“…Similarly, pairing a distinctive environment with the aftereffects of running produces a conditioned place preference in laboratory animals (Lett et al, 2000;Belke and Wagner, 2005). Exercise can also serve as a positive reinforcer, as both laboratory animals (Iversen, 1993;Belke, 1997;2000;Belke and Dunbar, 2001) and in-patient clinical populations (Schebendach et al, 2007) will perform an operant response that leads to the opportunity to exercise.…”
Section: Introductionmentioning
confidence: 99%